Climate resilience in rural Zambia: evaluating farmers' response to El Niño-induced drought. (26th October 2021) - Alfani, Federica; Arslan, Aslihan; McCarthy, Nancy; Cavatassi, Romina; Sitko, Nicholas
Abstract: This paper aims at identifying whether and how sustainable land management practices and livelihood diversification strategies have contributed to moderating the impacts of the El Niño-related drought in Zambia. This is done using a specifically designed survey called the El Niño Impact Assessment Survey, which is combined with the Rural Agricultural Livelihoods Surveys, as well as high resolution rainfall data at the ward level over 34 years. This unique panel data set allows us to control for the time-invariant unobserved heterogeneity to understand the impacts of shocks like El Niño, which are expected to become more frequent and severe as a result of climate change. We find that maize yields were substantially reduced and that household incomes were only partially protected from the shock thanks to diversification strategies. Mechanical erosion control measures and livestock diversification emerge as the only strategies that provided yield and income benefits under weather shock.